The role of advanced glycation end products in vascular aging: which parameter is the most suitable as a biomarker? - Mayer, Otto; Gelžinský, Július; Seidlerová, Jitka; Mateřánková, Markéta; Mareš, Štěpán; Svobodová, Veronika; Trefil, Ladislav; Cífková, Renata; Filipovský, Jan (Journal of human hypertension, 2021)
Advanced glycation end products (AGEs) are involved in several pathophysiologic processes in vascular diseases, including progressive loss of elasticity of the vessel wall (arterial stiffness). Circulating soluble receptors for AGEs (sRAGE) act as a decoy and counterbalanced the harmful properties of AGEs as the natural protective factor. We compared the role of circulating or skin-deposed AGEs and sRAGE regarding the natural course of arterial stiffening. In a prospective cohort study, we longitudinally followed 536 general population-based subjects (subsample of Czech post-MONICA study). Aortic pulse-wave velocity (PWV) was measured twice (at baseline and after ~8 years of follow-up) using a SphygmoCor device (AtCor Medical Ltd), and the intraindividual change in PWV per year (∆PWV/year) was calculated. Concentrations of sRAGE and carboxymethyl lysine (circulating AGEs) were assessed at the follow-up visit by ELISA, while skin AGEs were measured using the autofluorescence-based device AGE Reader. Using multiple regressions, we found significant association between ∆PWV/year as a dependent variable, and both, sRAGE and skin AGEs as independent ones (each on its own model). However, the closest associations to ∆PWV/year were found for the ratio of these two factors (skin AGEs/sRAGE) [β coeff = 0.0747 (SE 0.0189), p < 0.0001]. In a categorized manner, subjects with skin AGEs/sRAGE ratio ≥ 3.3 showed about twofold higher risk having ΔPWV/year ≥ 0.2 m/s [adjusted odds ratio was 2.09 (95% CI: 1.35-3.22), p = 0.001]. In contrast, neither circulating AGEs nor circulating AGEs/sRAGE showed any significant relation to ΔPWV/year. In conclusion, skin AGEs/sRAGE ratio seems to be a more sensitive biomarker of vascular aging than these single factors themselves or circulation status of AGEs.
Keywords: Aging; Receptor for Advanced Glycation End Products; lidé; receptor pro konečné produkty pokročilé glykace; prospektivní studie; Glycation End Products, Advanced; biologické markery; Prospective Studies; Biomarkers; stárnutí; produkty pokročilé glykace; Humans